Thermoregulatory responses in open water and pool swimming: presentation of hypothermia and hyperthermia within and outside of World Aquatics water temperature thresholds - Markey, K.; Galan-Lopez, N.; Esh, C.; Carter, S.; Chrismas, B.; Mountjoy, M.; Constantini, N.; Taylor, L. (Journal of Science and Medicine in Sport, 2025)
Background Water submersion challenges human thermoregulatory (Treg) homeostasis [typically a core temperature (TC) of ~37°C], accelerating rates of heat loss (cold water; hypothermia) and gain (warm/hot water; hyperthermia) when swimming, and increasing susceptibility to heat/cold illness. Particularly, during open water swimming (OWS) competition where race drop-out and fatalities occur within a broad mandated water temperature (Tw) range (16-31°C). Conversely, pool-based swimming (PBS) competition (performed within a narrow-mandated Tw range 25-28°C) schedules encompass circadian TC changes alongside multiple cycles of warm-ups, transition phases and races. Understanding Treg responses within OWS and PBS would: (i) enhance knowledge regarding swimmer`s Treg demands; (ii) inform competition health and safety policy from a heat/cold illness perspective; and (iii) underpin Treg orientated performance enhancement.